Integrating GIS and CA-MARKOV model in evaluating urban spatial growth - Narimah Samat, (Environmental Management Society, Malaysia, 2009)
The physical development is usually undertaken by an expansion of the urban fabric, with agricultural land and green fields on the fringe experiencing industrial and residential development. In Malaysia, for example, although planners know that amount of land needed to cater for urban population expansion, there is no systematic planning tool available to predict to location or the resulting pattern of such development on existing urban landscape. Thus, this study applies of Geographic Information System and CA-Markov model as a planning tool in evaluating urban spatial growth. The result suggests that this model can potentially be used along with existing planning document in order to evaluate the impact of the proposed planning policy on existing urban landscape